2008
DOI: 10.1056/nejmoa0800743
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tibolone in Older Postmenopausal Women

Abstract: Background Tibolone has estrogenic, progestogenic, and androgenic effects. Although tibolone prevents bone loss, its effects on fractures, breast cancer, and cardiovascular disease are uncertain. Methods In this randomized study, we assigned 4538 women, who were between the ages of 60 and 85 years and had a bone mineral density T score of −2.5 or less at the hip or spine or a T score of −2.0 or less and radiologic evidence of a vertebral fracture, to receive once-daily tibolone (at a dose of 1.25 mg) or plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
0
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(189 citation statements)
references
References 51 publications
6
151
0
13
Order By: Relevance
“…Clinical trials have demonstrated the efficacy of several medications to reduce the risk of breast cancer in women without preexisting cancer [20][21][22][23][24][25], but only tamoxifen citrate and raloxifene for 5 years are approved by the US Food and Drug Administration (FDA) for this purpose. It is also suggested that adjuvant tamoxifen for primary unilateral breast cancer treatment could reduce the risk of CBC in the general population [9].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have demonstrated the efficacy of several medications to reduce the risk of breast cancer in women without preexisting cancer [20][21][22][23][24][25], but only tamoxifen citrate and raloxifene for 5 years are approved by the US Food and Drug Administration (FDA) for this purpose. It is also suggested that adjuvant tamoxifen for primary unilateral breast cancer treatment could reduce the risk of CBC in the general population [9].…”
Section: Discussionmentioning
confidence: 99%
“…Eligible participants were required to have a natural menopausal history of 8-25 years and a BMD T-score of −2.0 or less at the lumbar spine using dual-energy X-ray absorptiometry (DXA). BMD T-score of −2.0 instead of −2.5 at the lumbar spine was selected based on consideration of overall clinical treatment efficacy in osteoporosis [4]. Exclusion criteria were: (1) previous exposure to toremifene, tamoxifen, droloxifene, lasofoxifene, or other investigational selective estrogen receptor modulators; (2) use of hormone replacement therapy within the past 3 months and use of the following medications within the previous 3 months: calcitonin or related products, raloxifene, sodium fluoride (at doses>2 mg/day), anabolic steroids, chronic oral glucocorticoid or related steroid, anticoagulant such as heparin (but excluding aspirin); (3) use of bisphosphonates during the past 24 months; (4) use of parathyroid hormone during the past 6 months; (5) use of any other investigational drugs during the past month; (6) radiographic evidence of more than three vertebral fractures; (7) current medical disease associated with the development of metabolic bone disease, including Paget disease, osteomalacia, bone marrow disease, hereditary disorders of calcium or mineral metabolism, adrenal disorders, poorly controlled diabetes mellitus (e.g., FBS>140 mg/dL), severe connective tissue disorders, gastrointestinal diseases, and obesity (BMI> 35 kg/m 2 ); (8) T-scores of the femoral neck or lumbar spine (L 1 -L 4 ) BMD more than 4.0 SD below the mean for young adults (T-score≤−4.0), lumbar spine ≤0.514 g/cm 2 (Hologic apparatus) or 0.654 g/cm 2 (GE Lunar apparatus), femoral neck ≤0.385 g/cm 2 (Hologic apparatus) or 0.400 g/cm 2 (GE Lunar apparatus); (9) current or past history of clinically significant hematological, endocrinological, cardiovascular, renal, hepatic, gastrointestinal, psychiatric, or neurological diseases or drug allergies to estrogen-like hormonal drugs; (10) screening laboratory abnormality exceeding the limits defined by the central laboratory; and (11) history of advanced scoliosis, osteoarthritis, or other clinical spinal deformity which would interfere with BMD measurement.…”
Section: Design and Participantsmentioning
confidence: 99%
“…Bisphosphonates, Metformin, Aspirin, other nonsteroidal anti-inflammatory drugs and COX-2 inhibitors, synthetic steroid hormone Tibolone, Statins, Fenretinide (derivative of retinoic acid), Rexinoids have shown promise in cohort study or randomized study. Table 4 summarizes newer agents showing promise for breast cancer prevention [27][28][29][30][31][32][33][34][35][36]. However, the results are not conclusive and should be interpreted with caution.…”
Section: Novel Agents In the Preventionmentioning
confidence: 99%